Component process analysis of verbal memory in a sample of students with a binge drinking pattern. (December 2020) - Gierski, Fabien; Stefaniak, Nicolas; Benzerouk, Farid; Gobin, Pamela; Schmid, Franca; Henry, Audrey; Kaladjian, Arthur; Naassila, Mickaël
Highlights: Student binge drinkers have reduced performance on learning a 24-word list. This is due to low proficiency in encoding, storage and retrieval processes. Memory processes are impacted by consumption speed and intoxication episodes. Academic failure described among binge drinkers could be partly related to findings. Abstract: Background: Many studies have emphasized the harmful impact of binge drinking on several cognitive functions, including memory. However, the exact nature of the memory processes involved is still unknown. The present study was designed to assess verbal working memory and verbal episodic memory, especially its encoding, storage and retrieval processes, in binge drinking to identify the processes impacted by this behavior. Methods: Participants were 48 community-recruited college students aged 18–25 years and categorized as either binge drinkers (BDs) or social drinkers (SDs). They were assessed with (a) subtests of the Wechsler scale (digit span, letter–number sequencing) measuring verbal working memory, and (b) a modified version of the Free and Cued Selective Reminding Test (FCSRT), which measures verbal episodic memory functioning in various conditions of encoding (controlled) and recollection (free recall, cued recall, and recognition). Results: Verbal working memory was unaffected by binge drinking, whereas verbal episodic memory performances were reduced. In particular, analysis of the modified FCSRT scores suggested that BDs had less proficient storage and retrieval processes. Furthermore, correlational analyses indicated that the proficiency of these memory components was negatively correlated with several indicators of binge drinking behavior. Conclusions: Results suggest that binge drinking behavior affects the storage and recollection processes of verbal episodic memory. The academic failure described in binge drinkers could be partly related to this harmful effect. Our results on the negative impact of binge drinking on memory should be used to develop information campaigns targeting students.